Micro-Irrigation and Solar Power: Unlocking India’s Agricultural Potential: Micro-Irrigation with Solar Power for Agriculture - Choudhary, Naseeb; Kumar, Suresh; Malik, DP; Kumar, Jitendra (Journal of Soil Salinity and Water Quality, 2025)
Water is vital for agriculture, but in India its availability is declining due to rising demand and climate variability. To address this, improving water productivity has become a priority. Integrating solar power with micro irrigation systems offers a sustainable way to enhance efficiency while reducing dependence on conventional energy. In this study, the potential area for micro-irrigation in India was estimated using two indices. The estimated potential area under micro-irrigation was approximately 88 Mha based on Index 1, which considered the proportion of the area irrigated by groundwater, tanks, other sources, and 30% of canal-irrigated land. Using Index 2, which included the proportion of the area irrigated by groundwater, tanks, other sources, and 50% of canal-irrigated land, the potential area was estimated to be approximately 93 Mha. MI adoption has grown at a Compound Annual Growth Rate of 9.75, reaching 16.73 Mha in 2023-24, with sprinkler irrigation covering 9.04 Mha (54.1%) and drip irrigation 7.68 Mha (45.9%). However, only 15.85% of the estimated MI ultimate potential (105.60 Mha) has been realized, with six states- Rajasthan, Maharashtra, Karnataka, Andhra Pradesh, Gujarat, and Tamil Nadu- accounting for 78% of MI adoption. Despite increasing solar pump installations (501,673 in 2022-23), their correlation with MI remains weak. Policies must address administrative inefficiencies, enhance incentives, and promote integrated solar-powered MI adoption to maximize sustainability and groundwater conservation.